Evaluation of Genetic Relationship between Trigonella-Melilotus complex Using CCMP Markers - Hora, Amandeep; Malik, C.P. (Plant Tissue Culture and Biotechnology, 2013)
To distinguish the taxa at the specific and varietal levels a range of DNA fingerprinting techniques are being employed. The objective of the current study was to establish the genetic correlation between the Trigonella-Melilotus complex i.e. M. indica, M. alba and Trigonella polyceratia using ten Consensus Chloroplast Microsatellite Primers (CCMPs). The polymorphism between the two genera indicated that they are intimately related and symbolize novel incongruity. Owing to less significant level of genetic variation, detected through CCMP, the differences between the two genera could be accredited to gene mutation or inconsequential chromosomal alterations. Plant Tissue Cult. & Biotech. 23(1): 59-66, 2013 (June)